8(x-6)=5x+3(x-16)

Simple and best practice solution for 8(x-6)=5x+3(x-16) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x-6)=5x+3(x-16) equation:


Simplifying
8(x + -6) = 5x + 3(x + -16)

Reorder the terms:
8(-6 + x) = 5x + 3(x + -16)
(-6 * 8 + x * 8) = 5x + 3(x + -16)
(-48 + 8x) = 5x + 3(x + -16)

Reorder the terms:
-48 + 8x = 5x + 3(-16 + x)
-48 + 8x = 5x + (-16 * 3 + x * 3)
-48 + 8x = 5x + (-48 + 3x)

Reorder the terms:
-48 + 8x = -48 + 5x + 3x

Combine like terms: 5x + 3x = 8x
-48 + 8x = -48 + 8x

Add '48' to each side of the equation.
-48 + 48 + 8x = -48 + 48 + 8x

Combine like terms: -48 + 48 = 0
0 + 8x = -48 + 48 + 8x
8x = -48 + 48 + 8x

Combine like terms: -48 + 48 = 0
8x = 0 + 8x
8x = 8x

Add '-8x' to each side of the equation.
8x + -8x = 8x + -8x

Combine like terms: 8x + -8x = 0
0 = 8x + -8x

Combine like terms: 8x + -8x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| c=.25m(r+z) | | 1/1+1/a/1/1-1/a | | 11t+3t-5= | | 7x+-2(x+-5)=3(x+-2)+-5x | | 3/4=4x-5/6 | | .2(x+5)=x+5 | | x+4=(x-4)2 | | z^2-7=-30 | | 3/4=4x-5 | | 3[z-(3z+18)+8]=5(z+5) | | 5(.666y+1.333)-4y=3 | | (4x-5/2)-(2x-1/6)=x | | 16x+24=7[x+6] | | (.6)y-4(9)=3-2y | | 32+2y=4 | | 3(15)+x=54 | | 54+6x+4(54-3x)=180 | | 2(z+1)-(5z-4)= | | (19b-6)-9(2b+4)=-2 | | 2(2)y+1=(2)y+3 | | 9x-8=16x+27 | | 12x+2.6=6.8x | | 54=3y+x | | 54=3x+y | | 2(x+9)=30+18 | | (19+3)2=x | | 5/4k=5 | | 54-3(45)= | | 5-2(4x-2)+2x= | | xa+5=7x+b | | -9(x+4)+2x+5=6x+11 | | Y=3*X+2 |

Equations solver categories